KALIMAT DAN KLAUSA PADA NOVEL LUBANG DARI SEPARUH LANGIT - Ressty Putri Ariyati; Muhammad Yusdi; Lindawati Lindawati (Linguistik : Jurnal Bahasa dan Sastra, 2020)
This research aim to describe a form, structure, and functions of sentences and clauses in novel Lubang dari Separuh Langit. Clause is a unit of grammatical in the form of a word group, consisting of at least subjects and predicates and potentially sentences. The purpose of this research  is described  a form, structure, and functions of sentences and clauses in novel Lubang dari Separuh Langit. The main theory used in the following analysis a form, structure, and functions of sentences and clauses in novel Lubang dari Separuh Langit are Ramlan (1987), Song (2001), Crystal (1991). Data in research was a  sentence and clause in novel Lubang dari Separuh Langit .The source of data was novel Lubang dari Separuh Langit   .To analyze data, used method of agih. Based on the result it can be concluded interogtive is a dominant sentence in novel Lubang dari Separuh Langit  .